Short-term weight reduction outcome after laparoscopic sleeve gastrectomy: A single center experience from Erbil, Iraq - Ismael, Nabaz H.; Shabila, Nazar (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: Laparoscopic sleeve gastrectomy has become the most common weight loss surgery worldwide. This study aimed to provide insights into the sustained effectiveness of laparoscopic sleeve gastrectomy in achieving weight loss over an extended period. Methods: This retrospective study was conducted on 116 obese individuals who underwent bariatric surgery in Erbil, Iraq, between May 2021 and May 2022. Baseline demographic and clinical data of the patients were collected. We documented participants’ weight trajectories over a 48-week follow-up. Results: The baseline mean weight decreased from 114.7 kg at the baseline to 101.7 kg at week 12 (P <0.001), 90.7 kg at week 24 (P <0.001), 82.4 kg at week 36 (P = 0.004), and 77.5 kg at week 48 (P = 0.348). A consistent and significant (P <0.001) reduction in weight change percentages was observed as the weeks progressed. The mean weight change percentage started at -11.2% in week 12 and progressively decreased to -32.1% in week 48. A consistent increase in the percentage of excess weight loss was observed as the weeks progressed, starting at 36.3% in week 12 and progressively increasing to 41.1% at week 24 (P = 0.103), 44% at week 36 (P = 0.816), and 78.6% in week 48 (P <0.001). The percentage of excess weight loss was significantly higher among younger age groups, males, singles and those with no chronic diseases, each at different follow-up intervals. Conclusion: Laparoscopic sleeve gastrectomy participants experienced considerable and sustained weight loss for 48 weeks. Gender, age, marital status, and chronic conditions influenced weight fluctuation to varied degrees. These results offer important insights into the efficacy of laparoscopic sleeve gastrectomy in obesity management, particularly as a short-term way to control weight.